2008
DOI: 10.1177/1098214007313742
|View full text |Cite
|
Sign up to set email alerts
|

The Fairy Godmother—and Her Warts

Abstract: Evaluators sometimes wish for a Fairy Godmother who would make decision makers pay attention to evaluation findings when choosing programs to implement. The U.S. Department of Education came close to creating such a Fairy Godmother when it required school districts to choose drug abuse prevention programs only if their effectiveness was supported by "scientific" evidence. The experience showed advantages of such a procedure (e.g., reduction in support for D.A.R.E., which evaluation had found wanting) but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(43 citation statements)
references
References 46 publications
(43 reference statements)
1
42
0
Order By: Relevance
“…In our experience, the information from local research efforts is highly valued for its contextual relevance, and is perhaps more likely to be put into action through health programs. For KT researchers, developing processes to assist community-based organizations to adapt research to local circumstances may be the most helpful way to advance decision making in this area [23]. Further, increasing the rigor of local research may result in building a culture supportive of evidence-informed decision making.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, the information from local research efforts is highly valued for its contextual relevance, and is perhaps more likely to be put into action through health programs. For KT researchers, developing processes to assist community-based organizations to adapt research to local circumstances may be the most helpful way to advance decision making in this area [23]. Further, increasing the rigor of local research may result in building a culture supportive of evidence-informed decision making.…”
Section: Discussionmentioning
confidence: 99%
“…These mandates are intended to increase the use of EBP by those who receive funding. As recently as 2011, studies have demonstrated that mandating use can have a positive influence on the employment of EBP (see Rieckmann, et al 2011, and Weiss, et al, 2008 for discussion). However, the converse side of the argument demonstrates pushback from implementers about the dangers of “cookie cutter” type approaches that may develop when top-down mandates are used (Dopson, Locock, Gabbay, Ferlie, & Fitzgerald, 2003; Jette, et al, 2003; McGowan, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Policy-makers operate under temporal, resource, and cognitive constraints, giving rise to a limited, or bounded, form of rationality (Cairney 2016). Crisis and controversy often preclude the luxury to fully assess the rigour of new evidence (Weiss et al 2008). Besides, evidence by itself is not enough to determine the appropriate course of action, even if it is perfectly understood (Cairney 2016).…”
Section: Conceptual Issues With Evidence-based Policy-makingmentioning
confidence: 99%
“…Even though an incremental, or ''enlightenment,'' model is a more accurate portrayal of how evidence can and does flow into the policy process (Amara et al 2004;Head 2010;Weiss 1977), it is similarly an ineffective basis for an EBPM appeal to policymakers. Given time constraints and incentives of the electoral system (see Cairney 2016;Weiss et al 2008), policy-makers are unlikely to be particularly interested in an interpretation of EBPM that can promise only the possibility of subtle incremental benefits over the long term. If academics want the policy process to change, it is problematic that classic portrayals of EBPM's social benefits are not intuitively persuasive to the policy-maker audience that must ultimately be convinced.…”
Section: Conceptual Issues With Evidence-based Policy-makingmentioning
confidence: 99%